Digital educational content in foreign language education - Daniyarova Gulmira Dalelkhankyzy, Sholpan Zhubanova, Khalel Agnur, (Opción, 2020)
The paper reviews recent investigations in digital foreign language education in preparation of professionally competent specialists having knowledge-based and language skills in the specialty and digital skills in using multimedia educational technologies. We identified basic sub-competences that forms professional intercultural competence of students in digital learning format. Besides, it is presented some digital methodological components (spheres, topics, subtopics, stages, a set of web-based interactive exercises) that form multimedia tutorial in educational platform TurboSite, using virtual learning environment and personal learning network. The author described multimedia/digital exercises and gave some samples, which are used in experimental part of the scientific thesis.